Memory, Trauma and World Politics Reflections on the Relationship Between Past and Present - Bell, D.; Bell, D. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2006)
Memory, Trauma and World Politics focuses on the effect that the memory of traumatic episodes (especially war and genocide) has on shaping contemporary political identities. Theoretically sophisticated and empirically rich, this book is an incisive treatment of the ways in which the study of social memory can inform global politics analysis.